Study of placentation and maternal and fetal outcomes in cases of 2 or more caesarean sections - Poonia, Supriya; Satia, Meena Naresh; Bang, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The CS epidemic is a reason for immediate concern and there is increase in repeat CS as well these days. The secondary increase in repeat CS delivery has been associated with increase in CS complications particularly increase in complications associated with abnormal placentation. Methods: It is a Prospective observational study which was conducted at a tertiary care centre over a period of 18 months with a sample size of 60 patients. Patients with two or more previous CS irrespective of parity index, gestational age, previous vaginal delivery or vaginal birth after CS, associated medical or surgical problems were included in the study. Intra-partum, postpartum complications, abnormal placentation, maternal and perinatal outcomes associated with previous 2 CS were studied. Any case less than 2 CS were excluded. Results: In this study, radiologically, 50 patients had no abnormality. 7 patients had placenta previa, 2 patients had placenta percreta and 1 patient had placenta previa with placenta accreta. These included abnormal placentation diagnosed radiologically by ultrasonography, colour Doppler or MRI. Intra-operatively, 49 patients had normal placentation. 6 patients had placenta previa without any evidence of placental adherence, 3 patients were placenta percreta. 1 patient had placenta previa with placenta percreta and 1 had placenta previa with placenta increta. Statistically significant differences p <.05 was observed in group of normal and abnormal placentation, with respect to type of anesthesia spinal/GA, uterine incision(pfannensteil versus midline and classical), bladder injury, intraoperative blood loss, uterine and internal iliac artery ligation, obstetric hysterectomy, placenta kept in situ, surgical site infections, neonatal resuscitation required and NICU admissions. Conclusions: The incidences of abnormal placentation have increased with the rise in previous two CS Also the maternal and perinatal morbidity and mortality increases with history of previous two CS.